Entrepreneurial Orientation of Born Global Firms in Turbulent Environment - Yang, Man (My University, 2013)
Since the international business environment has become rather turbulent, it is important to study Born Globals in turbulent environment. This research fills in the research gap and focuses on the research question how Born Globals could utilise entrepreneurial orientation to improve performance. Three research objectives are formulated to answer the research question. The first objective is to examine to what extent Born Globals adopt entrepreneurial orientation in turbulent environment and what dimensions are important. The second objective is to examine how dimensions of entrepreneurial orientation affect Born Globals’ performance in turbulent environment. The third objective is to investigate the factors that influence the entrepreneurial orientation and performance relationship. A qualitative research with multiple case studies was conducted. Four Finnish Born Globals in energy sector were selected as research sample. The empirical data were mainly collected from semi-structured interview with top management member of each company. Based on the empirical results, it is proposed that Born Globals adopt strong entrepreneurial orientation in turbulent environment, and their entrepreneurial orientation includes: innovativeness, proactiveness, risk-taking, flexibility and agility. It is suggested that innovativeness, proactiveness, flexibility and agility are important dimensions which positively affect Born Globals’ firm performance in turbulent environment; Risk-taking has to be well managed, otherwise high risk-taking may negatively affect Born Globals’ firm performance in turbulent environment. Moreover, it is proposed that environmental turbulence, product portfolio, and decision making logic moderate the relationship between entrepreneurial orientation and Born Globals’ firm performance. Among Born Globals with high entrepreneurial orientation, lower environmental turbulence, broader product portfolio in wider business segments, more effectuation-based decision making logic are associated with stronger firm performance respectively.
Keywords: Entrepreneurial Orientation; Born Globals; Turbulent Environment; Effectuation; Performance; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|